2003
DOI: 10.1128/jcm.41.2.592-600.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New Quantitative ompA -Based Real-Time PCR TaqMan Assay for Detection of Chlamydia pneumoniae DNA in Respiratory Specimens with Four Conventional PCR Assays

Abstract: Chlamydia pneumoniae, an important respiratory pathogen, is difficult to culture, and detection rates by conventional PCRs vary considerably. A new quantitative ompA-based real-time PCR assay based on TaqMan technology for detection of C. pneumoniae in respiratory samples is described, and its performance in terms of sensitivity and reproducibility is compared with those of four published conventional PCRs (one single-step PCR targeting a cloned PstI fragment; two nested PCRs, one targeting the 16S rRNA gene f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 23 publications
2
66
0
Order By: Relevance
“…The C pneumoniae-specific OmpA gene-based real-time PCR, the assay on which we relied, is the most sensitive. 3 In our study, we also analyzed 11 samples with 16S broad range rRNA PCR to confirm our findings.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…The C pneumoniae-specific OmpA gene-based real-time PCR, the assay on which we relied, is the most sensitive. 3 In our study, we also analyzed 11 samples with 16S broad range rRNA PCR to confirm our findings.…”
supporting
confidence: 59%
“…The range of C pneumoniaepositive patients varies greatly across studies from 0% to 100%. Apfalter et al 3 reported that 89% of all patients studied had C pneumoniae-specific antibodies, but the pathogen was not detected in a single carotid atheroma by real-time PCR and cell culture in carotid endarterectomy samples. So far, none of the studies have reported the presence of C pneumoniae in thrombus aspirates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The assays reported in the literature are in-house tests, and most have not been validated compared with culture or even other PCR methods (4). There is evidence of major problems with both inter-and intralaboratory reproducibility (6)(7)(8)(9). Much of the variation in the prevalence of C. pneumoniae DNA detected in human atheroma specimens reported in the literature (0-100%) is thought to be due to variation in methods, although true variation by type of specimen or population studied cannot be excluded.…”
Section: Review Of C Pneumoniae Serology and Detection Methodsmentioning
confidence: 99%
“…Real-time PCR is an effective method for detecting C. pneumoniae using induced sputum [11]. The major outer membrane protein (MOMP) gene has previously been shown to be a good genetic marker for C. pneumoniae in other real-time PCR-based studies [12,13].…”
mentioning
confidence: 99%